The Credit Crunch in East Asia : What Can Bank Excess Liquid Assets Tell Us? - Agenor, Pierre-Richard (World Bank, Washington, DC, 2014)
The authors propose a two-step approach for assessing the extent to which the fall in credit in crisis-stricken East Asian countries was a supply- or demand-induced phenomenon. The first step involves estimating a demand function for excess liquid assets held by commercial banks. The second step involves establishing dynamic projections for the periods after the crisis and assessing whether or not residuals are large enough to be viewed as indicators of an "involuntary" accumulation of excess reserves. The results for Thailand suggest that the contraction in bank lending that accompanied the crisis was the result of supply factors. Thai firms (presumably small and medium-size ones) faced binding constraints in getting access to credit markets after the crisis.